SELF-EFFICACY DAN KEMAMPUAN BERFIKIR KRITIS MATEMATIS SISWA DALAM PEMBELAJARAN MATEMATIKA - Nabila, Syahla; Tina Sri Sumartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between self-efficacy and students’ mathematical critical thinking skills in mathematics learning using an inquiry approach. Mathematical critical thinking skills involve the ability to analyze, evaluate, and construct logical solutions to mathematical problems, while self-efficacy refers to an individual’s belief in their ability to complete academic tasks, which plays an important role in shaping students’ motivation, attitudes, and learning persistence. This study employed a quantitative approach with a correlational design to examine the relationship between the two variables. The sample consisted of 25 seventh-grade students selected through purposive sampling. The research instruments included an essay test to measure students’ mathematical critical thinking skills and a Likert-scale questionnaire to assess students’ self-efficacy. Data analysis was conducted using the Shapiro-Wilk normality test and correlation analysis to determine the relationship between variables. The results showed that the correlation coefficient was r = 0.019 with a significance value of p = 0.928 (> 0.05), indicating that there is no significant relationship between self-efficacy and students’ mathematical critical thinking skills. However, the positive direction of the relationship indicates a tendency that higher self-efficacy may be associated with higher critical thinking skills, although at a very weak level. This study offers a novel contribution by revealing that, within an inquiry-based learning context, self-efficacy does not necessarily translate into higher mathematical critical thinking skills, challenging the common assumption of a direct positive relationship between the two variables. These findings suggest that mathematical critical thinking skills are not solely influenced by self-efficacy, but also by other factors such as learning strategies, learning environment, and practice intensity. Therefore, further research is needed to examine these factors more comprehensively.